Efikasi Diri, Harga Diri, dan Kepemimpinan Diri terhadap Kinerja Pegawai dalam Respons Darurat Bencana di Kabupaten Seram Bagian Barat - Manda Melina Kamelane; Wahab Tuanaya; Elake Nataniel (MAN 4 Kota Pekanbaru, 2025)
This study examines the influence of self-efficacy, self-esteem, and self-leadership on employee performance in disaster emergency response within West Seram Regency. The research employs a descriptive–quantitative approach with a causal-correlational design, conducted at the Regional Disaster Management Agency (BPBD) over a two-month period. The population consists of 50 employees, from which 44 respondents were selected using the Isaac and Michael sampling table at a 95% confidence level through simple random sampling. Data were analyzed using multiple linear regression. The results indicate that self-efficacy has a significant independent effect on employee performance during emergency operations. Self-esteem also contributes to performance variations, while self-leadership exerts a partial influence on performance outcomes. Furthermore, the three psychological variables collectively have a simultaneous and significant impact on employees’ effectiveness in handling disaster emergencies in West Seram Regency.